UJI KEKERASAN BAJA KONSTRUKSI ST-42 PADA PROSES HEAT TREATMENT - Akhmad Syarief (INFO-TEKNIK, 2006)
In metalurgy term, especially the steel should have certain characters, for example anti wear resistancause of friction and has hard surface. Getting such components within their characters, it is need a heat treatment process in addition for getting hard surface and strength of the steel itself. Heat treatment process basically consists of some steps, at first, heating up to a certain temperature, then colding at certain speed.In this research has been done heat treatment process, it is a heating steel at the temperature 8500C and holding for 30 minutes at this temperature for some seconds, then colding by soaked it into the water in which 270C temperature so there is no enough time for austenit to change become pearlit and ferrit or pearlid and cementit, but austenit changes into martensit directly.Maximum hardness will be reached after heat treatment process is interfered by more carbon, the higher carbon in it the higher hardness will be gotten. And the result is the hardness value after heat treatment process higher compare than before the heat treatment process has been done..